Juvenile Disseminated Paracoccidioidomycosis in an Immunocompetent Young Patient: A Case Report - Mota, Joseli Aparecida Braga; Avila, Carolina Oliveira de; Silveira, Daniela Marin Machado; Teixeira, Gabriel da Silva; Mendonça, Victória de Paula; Pereira, Lynea Glasyele Honorato; Santos, Patricia Roberta dos; Silva, Rodrigo Aparecido (Brazilian Journal of Case Reports, 2025)
Paracoccidioidomycosis (PCM) is a systemic fungal infection endemic to Latin America, caused by thermally dimorphic fungi of the Paracoccidioides genus. The juvenile form, although less common, presents a diagnostic challenge due to its nonspecific symptoms and frequent absence of pulmonary involvement. We report the case of a 20-year-old male from an endemic region in Brazil who presented with persistent afternoon fever, significant cervical lymphadenopathy, and weight loss. Initial investigations raised suspicion of lymphoma, but histopathological examination of a cervical lymph node biopsy revealed chronic granulomatous lymphadenitis with fungal structures consistent with PCM, confirmed by special stains (Grocott, PAS, and HE). The patient was treated with oral itraconazole 200 mg/day, with favorable clinical response after four weeks. This case underscores the importance of including PCM in the differential diagnosis of prolonged febrile syndromes with lymphadenopathy in endemic areas, highlighting the value of histopathological analysis and early antifungal therapy.